Plasmon Coupling Within the Multifold Nanorod Metasurface for Sensing Applications - Chien-Ying Huang; Hung-chun Chang (IEEE Photonics Journal, 2019)
A novel design for improving the sensing performance of localized surface plasmon resonance based nanosensors is proposed. We analyze the Fano-like coupling interaction within the multifold gold nanorod metasurface. By means of such Fano-like coupling effects, we can enhance the figure of merit (FoM) of nanosensors based on gold nanorod array by nearly one order. The main idea of our design can be easily adjusted for other nanophotonic platforms, and provides new possibilities for improving the performance of a myriad of applications, such as slow light devices, and optical switches.